Is ozone production able to explain the good performance of CabECO® technology in wastewater treatment?. (10th November 2021) - Rodríguez-Peña, M.; Barrios Pérez, J.A.; Llanos, J.; Saez, C.; Barrera-Díaz, C.E.; Rodrigo, M.A.
Highlights: CabECO® cells can be successfully used as electro-ozonizers. Need for high availability of oxygen to reach high efficiencies. Need for temperature regulation to improve efficiency. Very important role of ozone scavengers reflected on a decay in ozone concentration. Abstract: This work intends to go a step further in the application of electrochemical technology to produce ozone, by evaluating the production of ozone with a commercial cell registered as CabECO®, which has been previously used to disinfect heavily polluted water in a successful manner, with a view to ascertaining whether this success may be related to the production of ozone. The CabECO® cell is a PEM electrolyzer; that is to say, one in which anode and cathode are connected through a PEM membrane. Since ozone production on the electrolyte is important and depends on the composition of the liquid, attention must be paid to the electrochemical production of scavengers. Dosing of oxygen as microbubbles has a very positive effect on the production of ozone, while temperature regulation is as well considerably important, as the increase in temperature generated by ohmic losses can lead to important decreases in the efficiency of ozone electrogeneration. Rates within the range 0.06–0.60 mg O3 min −1 are observed; this means that the maximum current efficiency reached is as high as 6.11% (considering oxygen as raw matter). These results are extremely promising as compared with other references in the literature, at once they also indicate there is room for further improvements and a long way to prevent the effect of scavengers and increase the efficiency of the process. Graphical abstract: Image, graphical abstract